The Impact of Brand Image, Customer Experience, and Promotional Offers on Customer Loyalty in Technology Companies in Jakarta - Affifatusholihah, Lina; Sari, Titis Nistia (West Science Journal Economic and Entrepreneurship, 2024)
This study investigates the impact of brand image, customer experience, and promotional offers on customer loyalty within the technology sector in Jakarta. Given the competitive environment, understanding these determinants is essential for technology companies seeking to retain customers and foster loyalty. Using a quantitative approach, data were collected from 220 respondents through structured questionnaires measured on a Likert scale of 1 to 5. Structural Equation Modeling-Partial Least Squares (SEM-PLS 3) was employed for data analysis. Results show that all three factors significantly and positively affect customer loyalty, with promotional offers demonstrating the strongest influence, followed by brand image and customer experience. These findings emphasize the importance of strategic branding, superior customer engagement, and value-driven promotional offers in cultivating loyalty. The study provides practical recommendations for managers to enhance loyalty by leveraging these factors effectively.